Bentuk Reciprocity Dalam Produksi Berita Kriminal (Kajian Kriminologi Budaya Terhadap Redaksi Pos Kota) - A Yoseph Wihartono (Jurnal Kriminologi Indonesia, 2017)
In the process of news production, there’s a reciprocity aspect between journalists andnews resource that determine how the news will be reproduced and represented. Culturalcriminology criticizes the construction form of a news, the focus raised in this paper is thereciprocity aspect that mutually benefits both parties between the criminal journalist andthe police institution. The police will always provide information, facilitate access, andnews material to criminal journalists, the police are the ones who dominate the informationand sources of crime news. Conversely, criminal journalists tend to framing with a positiveimage (good police) against the main source, the police institution. This paper analyzes thereciprocity aspect of mass media editorial of Pos Kota online. The result of the analysis showsthat reporting of criminal journalist of Pos Kota online tends to reproduce and representpositive image of police institution (good police) repeatedly and with certain pattern to keeppositive image remain present positively. Therefore, the reciprocity relationship betweenjournalist and its news source has an effect on how a mass media doing framing.